PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH PACLOBUTRAZOL DAN DOSIS PUPUK SP-36 PADA PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L. ). - Fatmawati, Ayu; Sulistyono, Agus; Suhardjono, Hadi (JURNAL AGROTROPIKA, 2025)
This research aims to determine the effect of concentrations of Paklobutrazol and SP-36 fertilizer on the growth of peanut plants (Arachis hypogaea L.). This research was carried out in October 2023 – January 2024 at the Dsn Baban Barat Land in Blega Bangkalan, East Java. This research is a factorial experiment which was prepared using a Completely Randomized Design (CRD) with 3 replications. The first factor is the provision of Paklobutrazol ZPT and the second factor is using SP-36 fertilizer Factor I: Paclobutrazol (P) concentration which consists of 4 levels: P0 = 0 ppm, P1 = 100 ppm, P2 = 200 ppm, P3 = 300 ppm and Fakor II = SP-36 fertilizer dose consisting of 3 levels: S0 = 150 kg/ha, S1 = 200 kg/ha, S2 = 250 kg/ha. The parameters observed were plant height, number of leaves (strands), age at flower emergence, number of pods planted, number of filled and empty pods, weight of pods planted, weight of seeds planted. The research results showed that the Paklobutrazol concentration treatment gave a positive response to the specified parameters, including plant height, number of leaves (strands), age at flower emergence, number of pods planted, number of filled and empty pods, weight of pods planted, weight of seeds planted. The highest average yield of pod weight per plant was in the P1 concentration treatment, namely 100 ppm (33.78 gr). The Paklobutrazol concentration treatment also produced a very significant effect on seed weight per plant. The highest was in the P1 concentration treatment, namely 100 ppm 28.50 gr. The SP-36 fertilizer dose treatment had a significant effect on the number of pods, the weight of the pods planted and the weight of the seeds planted. However, the parameters of plant height, number of leaves (strands), age at flower emergence, number of filled and empty pods, had no real influence. The results of the combined data analysis from both gave a positive response to observations of the number of pods, the weight of the pods planted and the weight of the seeds planted.